Palace commandant V. N. Voeikov and the Duma-military opposition: confrontation during the First World War - M. A. Knyazev (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses the struggle of opposition Duma and military leaders against the palace commandant V. N. Voeikov during the First World War. The hyperbolized view of the role and influence of the general at court, his inclusion in the list of «irresponsible influences» became the reason for the declaration of «war» to the palace commandant by public and military forces. On the basis of the study of archival materials, sources of personal origin, materials of paperwork, the article identifies the goals, mechanisms and results of the struggle against Voeikov as an active member of the «court camarilla». The author comes to the conclusion about the evolution of forms and methods of combating the tsarist encirclement in 1914–1917: from attempts to «peacefully» remove or move to another position to apply radical measures (public and newspaper bullying, baseless charges, arrest)